THE ESSENCE OF THE ISLAMIC FAMILY - Koko Komarudin (Universitas Islam Negeri (UIN) Mataram, 2020)
The discussion of the Islamic family means discussing the families that are scattered all over the world where Islam is part of the religion followed by the population. Islamic family law (al Akhwal al Syakhsiyyah) is the main part of Islamic law with a larger portion and high enough attention, both from the heavens, namely divine revelation (Al-Qu'ran) and the Sunnah of the Prophet Muhammad as well as from the applicable laws and regulations in each country. . Islamic family law is basically here to provide a comprehensive and integral understanding and insight into how to have a family in accordance with Islamic rules. The aim is to provide assistance so that they can subside or prevent sources of disputes among family members and even offer ways to solve all the problems that occur and are faced by every Muslim family. The essence of the Islamic family is an ideal of the embodiment of the family which bases all activities and communication and interactions both in peaceful conditions and in an atmosphere of dispute on Islamic rules derived from the Al Quran and hadith. With regard to an Islamic family in a country, he cannot escape from binding rules such as the Marriage Law and the Compilation of Islamic Laws. This is in order to realize the noble ideals of the Islamic family, namely to build a sakinah family, mawaddah warahmah. The Islamic family does not mean that it does not face challenges and strife. However, the Islamic family always tries to resolve every case, problem, and conflict that occurs between family members by referring back to the Al-Qur'an and hadith and if necessary, the parties concerned such as the Office of Religious Affairs (KUA) and the Religious Court (PA) be involved in solving the problem. The final hope is that all activities that occur in the Islamic family can represent all maqashid al-syari'ah, namely hifdz al inen, hifdz al nafs, hifdz al aql, hifdz al nasl and hifdz al maal.